1976
DOI: 10.1016/0024-3205(76)90213-7
|View full text |Cite
|
Sign up to set email alerts
|

Mixed depressant and stimulant actions of morphine and their relationship to brain acetylcholine

Abstract: Morphine and related narcotic agonists produce mixed depressant and/or stimulant effects in a wide variety of animals including man (1,2). These effects are not only species but also time and dose related. It is not gener ally appreciated that even a single dose of morphine in a given species, such as the rat, may have initial depressant and subsequent stimulant effects. We believe this is an extremely important concept and intend to provide evidence of its wide applicability in the pharmacology of narcotics .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Morphine and other mu opioids, when administered acutely to rats, produce a biphasic effect on locomotion, with an initial decrease in locomotion during the first hour of testing, followed by a delayed increase over the next 2-3 h (Babbini and Davis 1972;Babbini et al 1975;Domino et al 1976;Vasko and Domino 1978;Brady and Holtzman 1981;Bartoletti et al 1987;Trujillo and Swadley-Lewellen 1997;SwadleyLewellen et al 1998). With chronic administration there is a decrease in the locomotor depression (tolerance) and an increase in the locomotor stimulation (sensitization) (Babbini and Davis 1972;Babbini et al 1975;Domino et al 1976;Vasko and Domino 1978;Brady and Holtzman 1981;Bartoletti et al 1987;Trujillo and Swadley-Lewellen 1997;. Thus, although the dependent measure in each case is locomotion, different phases of morphine's effects must be examined in order to study tolerance and sensitizationtolerance to locomotor depression must be studied during the early phase of morphine's effects, and sensitization to locomotor stimulation must be studied during the later phase.…”
Section: Discussionmentioning
confidence: 93%
“…Morphine and other mu opioids, when administered acutely to rats, produce a biphasic effect on locomotion, with an initial decrease in locomotion during the first hour of testing, followed by a delayed increase over the next 2-3 h (Babbini and Davis 1972;Babbini et al 1975;Domino et al 1976;Vasko and Domino 1978;Brady and Holtzman 1981;Bartoletti et al 1987;Trujillo and Swadley-Lewellen 1997;SwadleyLewellen et al 1998). With chronic administration there is a decrease in the locomotor depression (tolerance) and an increase in the locomotor stimulation (sensitization) (Babbini and Davis 1972;Babbini et al 1975;Domino et al 1976;Vasko and Domino 1978;Brady and Holtzman 1981;Bartoletti et al 1987;Trujillo and Swadley-Lewellen 1997;. Thus, although the dependent measure in each case is locomotion, different phases of morphine's effects must be examined in order to study tolerance and sensitizationtolerance to locomotor depression must be studied during the early phase of morphine's effects, and sensitization to locomotor stimulation must be studied during the later phase.…”
Section: Discussionmentioning
confidence: 93%
“…Low doses of morphine (1-2 mg/kg) produce hyperactivity (Fog 1970;Babbini and Davis 1972;Ayhan and Randrup 1973;Iwamoto 1981), whilst higher doses produce hypomobility, and at 20 mg/kg catalepsy is observed (Fog 1970;Babbini and Davis 1972;Domino et al 1976;Vasko and Domino 1978;Brady and Holtzman 1981). In addition, central application of DAGO to adult rats has been shown to either stimulate or inhibit locomotor activity depending on the doses employed (Locke and Holtzman 1986).…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the ability of morphine to modify locomotor activity, pain perception, and to induce reinforcing behavior is well documented (Kuschinsky and Hornykiewicz, 1974;Ling and Pasternak, 1983;Devine and Wise, 1994). Several studies in rats have shown that morphine causes dose-and time-related opposite effects on locomotor activity: typically, low doses increase it, while larger doses induce sedation and catalepsy (Babbini and Davis, 1972;Buxbaum et al, 1973;Domino et al, 1976). In contrast, morphine administration in mice produces a dose-dependent stimulation known as ''running fit'' syndrome.…”
Section: Introductionmentioning
confidence: 99%